Cholangioscopic classification of post‐living donor liver transplantation biliary strictures can predict their natural history and response to therapy. Issue 4 (19th October 2022) - Sharma, Zubin Dev; Karunakaran, Monish; Bansal, Rinkesh Kumar; Gandhi, Ashish; Singh, Manish Kumar; Soin, Arvinder Singh; Puri, Rajesh; Sud, Randhir
Abstract: Background: The study aimed to assess the morphology of post‐living donor liver transplant (LDLT) anastomotic biliary strictures using cholangioscopy and assess the impact of morphology on its prognosis. Methods: A single centre, prospective, observational study was conducted at a tertiary care teaching hospital from August 2014 to July 2016. Single operator cholangioscopy (SOC) was used to assess post‐LDLT anastomotic biliary strictures at presentation in 24 patients. Analysis included demographic and biochemical characteristics, time to stricture development, endoscopic procedural details, time to remodelling and development of recurrence on follow‐up. Results: Two distinct patterns of strictures were identified, type I with minimal inflammatory changes and type II with severe inflammatory changes. Guidewire cannulation was successful in 23 out of 24 (95.8%) patients. There was no significant difference between the two types of strictures based on aetiology of liver disease, CTP and MELD scores, time taken for the development or laboratory parameters at presentation. However, type II strictures required more sessions of dilatation (4 vs. 2; P  = 0.002), longer duration for resolution (282.5 vs. 201.5 days, P  = 0.095) and more number of stents. Conclusions: Addition of cholangioscopy tends to improve stricture cannulation rates at ERCP. It offers a useful classification of post‐LDLT strictures with prognostic and therapeutic significance. Type II strictures tend to require more sessions of endotherapy than type I strictures over a longer duration for remodelling. Abstract : Addition of cholangioscopy tends to improve stricture cannulation rates at ERCP, and offers a useful classification of post‐LDLT strictures with prognostic and therapeutic significance. Type II strictures tend to require more sessions of endotherapy than type I strictures over a longer duration for remodelling.